The Application of Tilawah Rhythms in Ornamenting Islamic Songs at Mahabbah Voice Studio, Payakumbuh Indonesia - Suci Mardiyah Hayati; Hengki Armez Hidayat (Program Studi Pendidikan Musik FBS UNP, 2026)
Objective: This study aims to analyze the use of Tilawah rhythms as ornamentation in Islamic songs, specifically in the song Bii Rasulillah at Mahabbah Voice Studio, Payakumbuh, focusing on musical characteristics, vocal techniques, and the expression of religiosity. Method: The study employed a qualitative approach with a content analysis method. The researcher served as the primary instrument, supported by writing tools and a camera to record audio and visual data. Data were collected through direct observation, literature review, interviews, and analysis of audio-video recordings of Bii Rasulillah. Data analysis followed steps of data collection, comprehension, coding, theme identification, and drawing conclusions. Results and Discussion: Findings indicate that Tilawah rhythms possess distinctive musical characteristics, structured melodic patterns, and diverse emotional nuances, supported by vocal techniques such as hight chest voice and proper breath control. Ornamentation in Bii Rasulillah includes the use of Bayyati, Hijaz, and Nahawand rhythms, integrating Tilawah and singing techniques in terms of melody inflection, dynamics, and vocal expression, producing a unique and religiously nuanced vocal character. Conclusion: This study confirms that integrating Tilawah rhythms as ornamentation in Islamic songs enriches singing techniques and shapes expressive, religiously inspired vocal performance, highlighting the potential of Tilawah as an aesthetic resource in contemporary Islamic music education.